(untitled) (Journal of Chitwan Medical College, 2026)
Introduction: Bronchiectasis is characterized by irreversible bronchial dilatation and leads to diverse pulmonary function impairment. While high-resolution computed tomography (HRCT) is the gold standard for structural diagnosis, spirometry assesses functional status. Data on the correlation between specific CT features and spirometry patterns locally are limited. Methods: A cross-sectional observational study was conducted at Chitwan Medical College, Nepal, over two months in 2023 using convenience sampling following ethical approval. Stable adult patients (>18 years) with HRCT-confirmed bronchiectasis were included. HRCT patterns (cylindrical, varicose, cystic, or fibrobronchiectasis) were compared for association with spirometry pattern (normal, obstructive, restrictive, or mixed) based on post-bronchodilator values. Chi-square test was used for association using IBM SPSS Statistics with 95% confidence interval (CI), and p<0.05 was considered significant. Results: Among 54 patients (mean age 57.83±16.23 years, 57.4% male), fibrobronchiectasis was the most common CT type (38.9%), followed by cystic and cylindrical types (27.8% each). The most frequent spirometry pattern was mixed (44.4%). There was no significant association between the type of bronchiectasis and the spirometry pattern (p=0.84). Bronchodilator reversibility was present in 5.5% of patients, with no significant association to the CT type (p=0.632). Conclusions: A mixed ventilatory defect was the most common spirometry finding. No significant association was observed between HRCT morphological types and spirometry patterns, highlighting the functional heterogeneity of bronchiectasis irrespective of structural subclassification.